Antarctic krill Thysanoessa macrura fills a major gap in marine lipogenic pathways - Kattner, Gerhard; Hagen, Wilhelm; Falk-Petersen, Stig; Sargent, John R.; Henderson R. James (Marine Ecology Progress Series, 1996)
The unique predominance of oleyl alcohols (18:1) is the striking characteristic of the lipids of the Antarctic euphausiid Thysanoessa macrura. The 2 isomers 18:1(n-9) and 18:1(n-7) occurred in similar proportions in the wax esters of T. macrura and comprised up to 80% of the total fatty alcohols. The remainder consisted mostly of the 20:1(n-9) alcohol along with small amounts of the 22:1(n-11) alcohol. No marine zooplankton species has previously been reported which produces wax esters with significant amounts of 18 carbon fatty alcohols. T. macrura specimens were collected in the high Antarctic Weddell Sea during autumn 1992 and summer 1993. Their lipid levels were high, about 40 to 50% of the dry mass with up to 70% of the total lipid as wax esters. The wax ester fatty acids were dominated by the saturates 14:0 and 16:0, which, along with the monounsaturate 18:1(n-9), accounted for more than 80% of the total fatty acids. Phospholipids contained high levels of (n-3) polyunsaturated fatty acids (20:5 and 22:6) typical of membrane lipids from marine zooplankton. The precise significance of the unique wax ester composition in T. macrura is not clear but this discovery underscores the biochemical adaptability of Antarctic zooplankton species to a constantly cold and highly seasonal polar environment.
Keywords: Sørishavet; Weddellhavet; biokjemi; dyreplankton; hoppekreps; krill; marin biologi; zooplankton; økologi

Predatory feeding behavior of an Antarctic marine copepod, Euchaeta antarctica - Yen, Jeannette (Polar Research, 1991)
Keywords: Antarktis; fytoplankton; hoppekreps; marin biologi

On the biology of some southern Copepoda - Ottestad, Per (I kommisjon hos Dybwad, 1932)
Publication Title: Hvalrådets skrifter : scientific results of marine biological research
Keywords: S.S.Vikingen; Sørishavet; Weddellhavet; hoppekreps; hydrografi; krill; marin biologi; plankton